2015
DOI: 10.2217/fon.15.174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene-Expression Profiling of CD133 + and CD133 - D10 Melanoma Cells

Abstract: We conclude that many genes involved in drug resistance and tumor aggressiveness are upregulated in CD133(+) D10 cells and targeting them might be an efficient strategy for treatment of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Roudi et al evaluated the genomic expression profile of D10 melanoma cells. In CD133 (+) D10 cells, many genes related to tumor aggressiveness were upregulated, including some of the genes in this study (Roudi et al, 2015). Our results suggest that CXCL10 may play a protective factor in lowering the risk of SKCM and trying to improve prognosis, while RXRG, SCG2 was affiliated with a poor prognosis in SKCM, a trying to find in line with previous reports of similar research, with resulting methods to be investigated further.…”
Section: Discussionsupporting
confidence: 89%
“…Roudi et al evaluated the genomic expression profile of D10 melanoma cells. In CD133 (+) D10 cells, many genes related to tumor aggressiveness were upregulated, including some of the genes in this study (Roudi et al, 2015). Our results suggest that CXCL10 may play a protective factor in lowering the risk of SKCM and trying to improve prognosis, while RXRG, SCG2 was affiliated with a poor prognosis in SKCM, a trying to find in line with previous reports of similar research, with resulting methods to be investigated further.…”
Section: Discussionsupporting
confidence: 89%
“…It seems to be related to pathways of tumor progression and aggressiveness (epithelial-tomesenchymal transition, EMT; Wnt signaling pathway) [33] and, as such, it has been associated with CSCs in different tumors [34]. However, conflicting results have been reported regarding its role in defining the CSC population in melanoma tumors [21,35,36].…”
Section: Surface Markersmentioning
confidence: 99%
“…Among the surface markers commonly used to identify melanoma stem cells are CD133, CD271, ABCB5, and ALDH1A [ 151 ]. CD133 has been associated with CSCs in different tumors including melanoma [ 151 , 152 ]. A previous study indicated that CD133 + CSCs isolated from the metastatic melanoma cell line D10 significantly induced and accelerated initial angiogenesis compared to CD133 − cells [ 117 ].…”
Section: Characterization Of Oral Non-scc Cancer Stem Cellsmentioning
confidence: 99%